(untitled) (JURNAL ADMINISTRASI PUBLIK, 2020)
The research has been intended to identify and analyze how a mutation affect the workforce of the workforce and the development of human resources in the western region of maluku. The method that the writer USES in this study is the asosiative research method based on a positivism philosophy, used by researchers in a particular population or sample. Sampling of samples used is accindendal sampling techniques of research in the body’s department and the development of human resources in maluku southwest of the west of 33. Analysis of data analysis is simple regression analysis and simple korelation analysis. Based on coronal corelation analysis (r) = 0.848 means the correlation of the two variables are positive and significant. Based on simple regression analysis got the y = 8.667 + 0,722 which means the relationship between the two variables is positive. Whereas from the testing initiative of determinations, the PFF was extracted by.0,72 or 72%. With the result it can be explained that the contribution to the spirit of work is 72% while the rest isa contribution to the other. According to the results of the initial test, f 79,379 was made to f table by 2.60 to the point of 0.05. From the data it’s got f is counting bigger than the f table where fcount 79,379 > 2.60. Then ho was rejected and ha received. It means that there is an influence between the variables of a mutation in the environment of the workforce and the development of human resources in the western region of maluku. Key Words: Mutations, Labor, Civil State Apparatus